GEOLOGY OF THE SUNGAI SIPUT (N) AREA AND ECONOMIC USES OF LIMESTONE - BINTI MAHAMUD, AMIRAH THAQIFAH (Universiti Teknologi PETRONAS, 2015)
The Kinta Valley area is surrounded by numerous limestone hills with numerous quarries operating for dolomite and construction materials needed for both domestic and international markets. This project is focused on a study of the geology of the Sungai Siput (N) area and the economic potential of the limestone deposits in the area. The objectives of the project are to produce a detailed scale (1:50 000) geological map of the Sungai Siput (N) area and to describe the lithostratigraphy of the limestone beds at an abandoned quarry. The study is divided into two parts which are the field mapping and sample collection for geochemical analysis. Geochemical analysis on selected limestone samples will lead to evaluate the economic potential of the limestone. Geological mapping shows that four types of rock exist in the study area which includes limestone, granite, schist and chert. The major fracture systems can be grouped into four along 080o-260o, 130o-310o, 090o-270o, and 100o-280o based on rose diagram analysis. The results from the analysis are discussed in terms of economic potential of the limestone in the study area. Based on the mineralogical analysis the limestones are described as unsuitable for dimension stone as the limestones are fine micritic limestone which is less durable. Based on chemical analysis, the LOI result shows that the limestone from Outcrop 1 can be classified as having high purity of 97.73% CaCO3 compared to limestone from Outcrop 2 which is classified as having low purity. From the XRF analysis, only limestone from Outcrop 1 has potential for cement manufacture and as lime for steel flux. However, based on the whiteness test, both limestones are unsuitable for paper fillers or paper coating. In terms of construction uses, limestones from both locations are suitable for road pavement, concrete and airfield pavement.